The Interaction between Technical Currency Trading and Exchange Rate Fluctuations - Stephan Schulmeister (Austrian Institute of Economic Research (WIFO), 2005)
This paper examines the mutually reinforcing interactions between exchange rate dynamics and technical trading strategies. I first show that technical trading systems have been quite profitable during the floating rate period. This profitability stems from the successful exploitation of exchange-rate trends and not from taking winning positions relatively frequently. I then show that technical models exert an excess demand pressure on currency markets. When these models produce trading signals, almost all signals are on the same side of the market, either buying or selling. When technical models maintain open positions they are either long or short. Initial exchange rate movements triggered by news or by stop-loss orders are strengthened by technical trading and are often transformed into a trend. This "multiplier effect" is reflected by the close relationship between technical trading signals and order flows. Hence, order flows are not only driven by (fundamental) news but also by technical trading, which reinforces exchange rate trends to which it responds.
Keywords: F31; G14; G15; 330; Exchange rate; Technical trading; Heterogeneous agents; Währungsspekulation; Wechselkurs; Wechselkurstheorie; Schätzung